PENGARUH KEPERCAYAAN DIRI DAN KOMUNIKASI INTERPERSONAL TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Priscilla Sintiawati Pangestu; Edwita Edwita; Ishak Gerard Bachtiar (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2019)
This study set an objective to determine the effect of self-confidence and interpersonal communication on the students’ critical thinking skills in District One Public Elementary School in Pasar Minggu. The method that was employed in this study was qualitative study with survey approach. The data analysis technique was path analysis. Path analysis was used to analyze the pattern of relationship in order to find out either direct or indirect effect of exogenous variable set towards the endogenous variable. The study employed random sampling with the population of some homogenous schools. Random sampling was selected randomly so that each participant in the sampling got an equal chance and opportunity to be selected to be the sample. The sampling process was conducted through the lottery. In this study, there were 120 students from 3 schools. The result of this study showed that self-confidence gave a direct impact to the students’ critical thinking skill; moreover, the interpersonal communication gave a direct impact to the students’ critical thinking skill; then, the self-confidence brought a direct impact to the students’ interpersonal communication.